Anesthesia and Developing Brains: Unanswered Questions and Proposed Paths Forward. (11th January 2022) - Ing, Caleb; Warner, David O.; Sun, Lena S.; Flick, Randall P.; Davidson, Andrew J.; Vutskits, Laszlo; McCann, Mary Ellen; O'Leary, James; Bellinger, David C.; Rauh, Virginia; Orser, Beverley A.; Suresh, Santhanam; et al.
Abstract : Anesthetic agents disrupt neurodevelopment in animal models, but evidence in humans is mixed. The morphologic and behavioral changes observed across many species predicted that deficits should be seen in humans, but identifying a phenotype of injury in children has been challenging. It is increasingly clear that in children, a brief or single early anesthetic exposure is not associated with deficits in a range of neurodevelopmental outcomes including broad measures of intelligence. Deficits in other domains including behavior, however, are more consistently reported in humans and also reflect findings from nonhuman primates. The possibility that behavioral deficits are a phenotype, as well as the entire concept of anesthetic neurotoxicity in children, remains a source of intense debate. The purpose of this report is to describe consensus and disagreement among experts, summarize preclinical and clinical evidence, suggest pathways for future clinical research, and compare studies of anesthetic agents to other suspected neurotoxins. Abstract : This report summarizes preclinical and clinical studies of anesthetic neurotoxicity in children, identifies consensus and disagreement among experts, and suggests paths forward to further ensure the safety of children undergoing procedures requiring anesthetic agents.